Effect of Stage Construction on Numerical Modeling of Layered Flexible Pavement System - Ghadimi, Behzad; Asadi, Hossein; Nikraz, Hamid (Research Publishing Services, 2012)
Stage construction in pavement system can be separated in two: (a) during construction of pavement layers (b) during performance of pavement system. The first case is about to consider the effects of compaction on base and sub-base. The second case is considering the removing of damaged asphalt layer and replacing it with a new layer. In this paper an in depth study has been done to investigate the effect of the first case on numerical modeling of the layered pavement system. The numerical model has been assembled in KENLAYER, CIRCLY and ABAQUS and the results of analysis are presented. A comparison has been done to indicate the difference between considering stage construction effects and ignoring it.